Notices (Blackfriars, 1934)
Thomas De Vio Cardinalis Caietanus, Scripta Philosophica, De Nominum Analogia. De Conceptu Entis. Editionem curavit P. N. Zammit O.P. De Motu Oxoviensi et de Anglo-Catholicis, auctore B. Lrcming, S.J. morality extracted from the Confessions of St. Augustine. By Pyre J. N. Grou, S.J., with an Introduction by Dom Roger Huddleston, O.S.B. The Biblefor Every Day. Selected and arranged by the Most Rev. Alban Goodier, S.J. The Imitation of Christ. By Thomas à Kempis. A revised translation based on Bishop Challoner's Text of 1737. Saint Benedict. By Abbot Cabrol. Translated by C. M. Antony. St. Conrad of Parzham. By Father Dunstan, O.S.F.C. Matt Talbot: The Irish Worker's Glory. By James F. Cassidy. 'Neath Fnglish Skies. By Frederick 1. Cowles, F.K.S. Scot. Catholic Club of New York. Catalogue of an Exhibition illustrative of the History of Literature.